Optimasi Biaya Distribusi Kusen Pintu Menggunakan Model Transportasi Northwest Corner Method, Russel Approximation Method, dan Stepping Stone - Poppy Andriani; Hendra Cipta (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
The transportation method is a method used to calculate distribution costs based on the origin that provides the same products to the destination location optimally using minimum costs. Previously, Cv Prima had to pay Rp 72,356,720 for transportation costs. So that the CV Prima company experienced swelling in distribution costs. Expenses for excess distribution costs result in the quality of door frame delivery not being optimal. In this study, the Northwest Corner Method and the Russell Approximation Method were used as the initial solution and continued with the Stepping Stone method as the optimal solution. So that this research produces the lowest costs after applying the Northwest Corner method revealing transportation costs of IDR 69,256,630 and using the Russel Approximation Method, transportation costs are IDR 67,304,680. For Stepping Stone optimization, the transportation cost is IDR 66,641,020. Therefore, the Northwest Corner and Russell Approximation Methods and continued with the Stepping Stone method for this problem are more efficient, because the company found a reduction in transportation costs of 7.899% or IDR 5,715,700.